Desenvolvimento de teste diagnóstico não invasivo capaz de detectar anticorpos anti-SARS-CoV-2 em urina - Fernanda Fonseca Ramos (2022)
The Enzyme-linked immunosorbent assay (ELISA) method has been widely used to detect anti-SARS-CoV-2 antibodies generated after exposure to the virus or vaccination. The sample usually used to perform the test is the serum. Thus far, no study has investigated the urine of patients as biological sample to detect specific SARS-CoV-2 antibodies. Urine is a biological specimen with significant advantages inherent to the type of sample, which comprises non-invasive collection, easy handling and storage. In this work, we propose an in house urine-based indirect ELISA using recombinant proteins from Nucleocapsid (N) and Spike (S) of the SARSCoV-2 virus. SARS-CoV-2 recombinant N and S protein subunits (Gly-S, NonGly-S1 and NonGly-RBD) were evaluated in an ELISA platform with a panel composed about 200 urine and serum samples. The presence of anti-SARS-CoV-2 antibodies in urine was detected with similar or superior sensitivity and specificity to serum, in which sensitivity values of 94.0%, 75.0%, 81.38% and 89.66% were obtained, while specificity values were of 100.0%, 96.0%, 96.77% and 96.77%, respectively, against rSARS-CoV-2 N, S-Glic, S1-NGlic and RBD-NGlic proteins. In conclusion, the data presented suggest that urine could be considered as a potential biological sample for application in immunodiagnostic platforms for SARS-CoV-2 infection, with benefits to the individual and population context.